Western Framings Versus the Lived Experience of Populations Exposed to Trafficking in South-south Nigeria - Igbinomwanhia, Osasere Greg (NIU Journal of Social Sciences, 2023)
Human and Sex trafficking issues represent contemporary global social problems which are yet to be solved. Women and young girls are particularly still exposed to the danger of maternal mortality, unwanted pregnancy, sexually transmitted diseases and other health and social consequences. Many victims suffer human rights abuses including confinement and effective captivity, physical and sexual assaults. Through human trafficking and sex trafficking, a nation’s active population is threatened and exploited with young people unable to attain their full potential. This has major implications for development impediments especially for source countries like Nigeria in Africa where a large number of young girls and women are annually recruited for sex work in Europe and other foreign countries. This research thesis uses qualitative research methods to explore tensions between Western framings of the phenomena and the lived experience of populations exposed to human trafficking in the area of study. Keywords:   Human and Sex trafficking, Western Framings, Lived Experience of Populations Exposed to the Phenomenon, Understanding Nature and Dynamics, Edo state, South-south Nigeria